Dificultades del aprendizaje en la lectura y escritura de los niños y niñas achuar de 6 a 12 años. Estudio de caso en el CECIB KAYANTSA - Titia Antun, Kashijint Pedro (2018)
The present titration work consists of an analysis about learning difficulties in reading and writing of Achuar children from 6 to 12 years old, case study in the CECIB Kayantsa. Therefore, this work aims to determine the main problems that children have in the learning process of both reading and writing. For this case study, we base ourselves on the theoretical foundation related to the conception of reading and writing, its process and learning problems, in addition we deal with the main difficulties in the educational process such as: dyslalia, dyslexia, dysgraphia, disortography and dyscalculia. For approximation to the case study, a qualitative approach is used. Therefore, the research collects direct information from children and their families through observation and interviews. During the case study it is evident that the main difficulties presented by children from six to twelve years of the Kayantsa Educational Center are: dyslalia, dyslexia, dysgraphia, disortography and dyscalculia. These difficulties were presented in the educational process. In the educational process, reading and writing are paramount at all levels of the pedagogical system, since they enable the training of children to access a more adequate, clear and efficient communication. However, one of the difficulties that children of education face in their school learning process is acquiring the habit of reading, and learning to express their ideas with cohesion, coherence, and adaptation to the communicative situation.